Karte von der Hudsons Bay und Strasse zur allgemeinen Historie der Reisen - Bellin, Jacques Nicolas, 1703-1772 ([Leipzig], 1758)
Black and white. Date on map: 1757. Relief shown pictorially. Prime meridian Paris. Decorative title cartouche. Bar scale in common French sea miles. CNS map no. 94.